2019
DOI: 10.1182/blood-2019-125332
|View full text |Cite
|
Sign up to set email alerts
|

Easix Is Strongly Associated with Complement Activation and Overall Survival in Adult Allogeneic Hematopoietic Cell Transplantation Recipients

Abstract: Introduction: Endothelial dysfunction is a common denominator of graft-versus-host disease (GVHD) and transplant-associated thrombotic microangiopathy (TA-TMA). The latter is also characterized by excessive complement activation. Recent studies have introduced the Endothelial Activation and Stress Index (EASIX) as a potential predictor of survival in patients with GVHD. We hypothesized that EASIX would predict complement activation and survival in patients with GVHD and TA-TMA. Methods: We enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In our study, we found significantly higher suPAR and GDF-15 levels in HSCT-TMA and GVHD patients compared to allo-HSCT and healthy controls. Moreover, both GDF-15 and suPAR concentrations were associated with EASIX at day 100 and the last follow-up, and these findings are comparable with our previous study where EASIX at the same time points was significantly higher in HSCT-TMA and GVHD compared with controls [ 63 ]. Interestingly, suPAR was associated with creatinine and platelets at day 100 and last follow-up, while GDF-15 was only associated with platelets at both time points.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we found significantly higher suPAR and GDF-15 levels in HSCT-TMA and GVHD patients compared to allo-HSCT and healthy controls. Moreover, both GDF-15 and suPAR concentrations were associated with EASIX at day 100 and the last follow-up, and these findings are comparable with our previous study where EASIX at the same time points was significantly higher in HSCT-TMA and GVHD compared with controls [ 63 ]. Interestingly, suPAR was associated with creatinine and platelets at day 100 and last follow-up, while GDF-15 was only associated with platelets at both time points.…”
Section: Discussionsupporting
confidence: 90%
“…To date, there is a lack of standardized laboratory parameters that specifically address endothelial dysfunction in these patients. The EASIX score, which is based on the calculation of LDH multiplied by Cr, divided by platelet count, has emerged as a potential prognostic biomarker of endothelial dysfunction in patients with HSCT-TMA and GVHD [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…EASIX score combines three routine laboratory tests that are used as diagnostic parameters of TA-TMA and is calculated using the following formula: (Lactate Dehydrogenase (U/L)) x (Creatinine (mg/dL))/Thrombocytes (10 9 cells per L). Elevated EASIX score at days 0 after HCT has been showed to predict the risk of mortality in patients with acute GVHD and TA-TMA ( 86 , 107 ). This easy-to-calculate index can be used by clinicians as a tool for clinical management of decision in patient with GVHD in the reduced conditioning regimen setting, since this index was not predictive in case of myeloablative conditioning regimens ( 86 ).…”
Section: Biomarkers Of Endothelial Activation and Damagementioning
confidence: 99%
“…The Endothelial Activation and Stress Index (EASIX)a composite measure of LDH, creatinine, and platelet levels-has demonstrated prognostic value for risk of death in patients with GVHD [114][115][116]. In adult patients with GVHD and HSCT-TMA, soluble C5b-9 levels were strongly associated with EASIX score 100 days after transplant and at last follow-up [115].…”
Section: Diagnostic and Prognostic Markers In Hsct-tmamentioning
confidence: 99%
“…The Endothelial Activation and Stress Index (EASIX)a composite measure of LDH, creatinine, and platelet levels-has demonstrated prognostic value for risk of death in patients with GVHD [114][115][116]. In adult patients with GVHD and HSCT-TMA, soluble C5b-9 levels were strongly associated with EASIX score 100 days after transplant and at last follow-up [115]. When EASIX was calculated before conditioning, the score was a significant prognostic factor for HSCT-TMA and was predictive of overall survival after HSCT, independent of other assessments [114].…”
Section: Diagnostic and Prognostic Markers In Hsct-tmamentioning
confidence: 99%